Should Denmark and Sweden join the banking union? - Svend Erik Hougaard Jensen; Dirk Schoenmaker (Bruegel, 2020)
An important policy discussion is ongoing in Denmark and Sweden on joining the Euro-pean Union's banking union. Joining would bring pros and cons. A major issue is the supervi-sion and resolution at the national level of large banks with a Scandinavian footprint. It is not evident that Denmark and Sweden would be able to resolve these large banks by themselves, if and when needed.The main rationale for joining the banking union is cross-border banking in the EU inter-nal market. The banking systems of Denmark and Sweden have similar cross-border char-acteristics to euro-area countries, suggesting that the rationale for joining is similar. It would also be a choice in favour of increased cross-border banking and less national banking,Moreover, both countries have large banks which may be too big to save at the national level, but not at the banking-union level. Next, joining banking union would put the large Danish and Swedish banks in a peer group of European banks. That would lead to more even-handed supervisory treatment and also facilitate comparative analysis by investors.Nevertheless, there are some governance concerns. While euro-area countries have an automatic and full say in all banking-union arrangements, the out-countries lack certain formal powers in ultimate decision-making. We find that this may in practice be less of a problem. Finally, the out-countries have the nuclear option of leaving the banking union.
Keywords: 330